1998
DOI: 10.1046/j.1365-2311.1998.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Prey species and prey diet affect growth of invertebrate predators

Abstract: 1. The effects of prey species and leaf age used by prey on performance of two generalist invertebrate predators were studied. The focal plant was Plantago lanceolata, which contains iridoid glycosides.2. Diet of the herbivorous prey influenced their growth rate. 3. The generalist herbivore (Vanessa cardui) and the novel-plant feeder (Manduca sexta) contained very low levels of iridoid glycosides in their haemolymph, whereas the specialist (Junonia coenia) levels were 50-150-fold higher.4. Predatory stinkbugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 57 publications
1
50
2
Order By: Relevance
“…We attribute the higher amount of feeding by the fifth instars to the physiological requirement that the fifth instars need more energy for imminent morphological and physiological development of reproductive organs. Strohmeyer et al [28] found that P. maculiventris females fed more than males, which is contradictory to our study. DeClercq and Degheele [29] also reported that mated P. maculiventris females consumed more prey than males.…”
Section: Discussioncontrasting
confidence: 99%
“…We attribute the higher amount of feeding by the fifth instars to the physiological requirement that the fifth instars need more energy for imminent morphological and physiological development of reproductive organs. Strohmeyer et al [28] found that P. maculiventris females fed more than males, which is contradictory to our study. DeClercq and Degheele [29] also reported that mated P. maculiventris females consumed more prey than males.…”
Section: Discussioncontrasting
confidence: 99%
“…This suggested that larvae of the first two preys presented more nutrients (e.g., proteins) for nymphs of this predator, thus improving their development. These results were similar to those observed for P. maculiventris which had bigger body weight of newly-emerged adults when its nymphs were fed on T. molitor larvae than on Junonia coenia Hubner, Vanessa cardui (L.) (Lepidoptera: Nymphalidae) or Manduca sexta (L.) (Lepidoptera: Sphingidae) caterpillars (Strohmeyer et al 1998). A positive correlation between the calorific value and larvae size of the alternative prey G. mellonella allowed obtaining heavier P. maculiventris females (Mukerji and LeRoux 1969).…”
Section: Performance Of Supputius Cincticeps With Different Preyssupporting
confidence: 85%
“…Lacerda et al (2004) recorded a development time of 19.03 days for P. nigrispinus fed on M. domestica larvae, which is similar to the results observed in the present study. According to Strohmeyer et al (1998), in addition to prey type, the quality of the diet of the prey affects the growth rate of some predators, including the pentatomids which as Podisus maculiventris (Say, 1832) (Heteroptera: Pentatomidae).…”
Section: Resultsmentioning
confidence: 99%